Handelsorientalisme i engelsk drama 1580-1630 - Fastrup, Anne (K&K - Kultur og Klasse, 2017)
The early modern Turco-Barbary plays of Christopher Marlowe, Robert Daborne and Philippe Massinger bear witness to how deeply England’s expanding trade with the Muslim Ottoman Empire affected English literature. Within few decades, a new catalogue of dramatis personae such as Turcs, Barbary pirates, English sailors who had converted into Islam, Jewish merchants and go-betweens, began to appear on the scenes of London’s commercial theatres. The purpose of this article is to discuss the particular mercantile character of this renaissance orientalism. Through the demonstration of how the theatrical representation of the encounter with the Muslim world was based on a moral suspiciousness or scepticism toward the merchant whose commerce depended upon foreign markets in goods and money, this article attempts to understand why conversion to Islam and cross-cultural movement becomes such a prominent feature in the English Turco-Barbary plays.